2020
DOI: 10.1186/s12876-020-01489-4
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the ascending colon during implantation of an indwelling peritoneal catheter: a case report

Abstract: Background Tunneled peritoneal drainage catheters are described as an effective and relatively safe method in the management of malignant and non-malignant refractory ascites. Therapeutic advantages, linked to their use, are self-management of ascites and palliative care at home. Complications occur rarely. We describe an ascending colon perforation after implantation of a peritoneal drainage in a patient with refractory ascites due to liver cirrhosis. Case presentation The 68-year-old male was admitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Peritoneal catheter complications accounted for 30.7% ( n : 8) of deaths. Of the few studies that evaluated this problem, most focus on specific cases [ 37 , 38 , 39 , 40 ]. The review by Li, Ng and Mcintyre revealed that different complications due to systemic peritoneal inflammation complications were factors that increased mortality [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal catheter complications accounted for 30.7% ( n : 8) of deaths. Of the few studies that evaluated this problem, most focus on specific cases [ 37 , 38 , 39 , 40 ]. The review by Li, Ng and Mcintyre revealed that different complications due to systemic peritoneal inflammation complications were factors that increased mortality [ 41 ].…”
Section: Discussionmentioning
confidence: 99%